Perancangan User Experience (UX) Aplikasi Manajemen Waktu Berbasis Mobile dengan Metode Design Thinking dan Human-Centered Design: User Experience Design for Time Management Mobile Application Using Design Thinking and Human-Centered Design Method - Kamalia Fitriana; Diah Priharsari; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Time management is a self-control of how long someone spend their time for certain activities, especially to get effectiveness, efficiency, and productivity. In the other hand, time management still being a big problem for people today. Lack of time management application and development skill is one of the reason that time management is difficult to implement. Because of this problem, researcher do a user experience design for time management mobile application. This application is designed with a combination of design thinking and human-centered design methods. Design thinking is used as a reference in design stage process, while human-centered design support the design process by its tool recommendation. The result of this design process is 6 kinds of pages namely login and sign up page, to-do list page, focus mode page, timer page, calendar page, time allocation page, and profile page. This application design was tested using usability testing. The result is 83% in effectiveness aspect and 78.4% in efficiency aspect. Meanwhile, the user satisfaction aspect gets 70% with as2nd Quartile on the quartil ranges, Marginal on the acceptability ranges, and Good on the adjective range.